The Role of Forensic Accounting in Detecting Financial Fraud in the banking sector - Muhammad Hasyim Ashari; M. Anas; Dwi Fitrianingsih (Pt. Anagata Sembagi Education, 2025)
This study explores the role of forensic accounting in detecting fraud within the banking sector, with a focus on its practices, challenges, and contributions to internal control systems. Using a qualitative case study approach, data were collected through in-depth interviews with key informants from major financial institutions, including Bank Negara Indonesia (BNI), Bank Central Asia (BCA), and oversight bodies such as the Financial Services Authority (OJK) and the Financial Transaction Reports and Analysis Center (PPATK). The findings reveal that forensic accounting plays a significant role in uncovering complex fraud schemes that are often undetected by conventional auditing processes. Techniques such as financial ratio analysis and forensic data analytics prove effective in identifying anomalies, while digital tools enhance the accuracy and efficiency of investigations. However, challenges such as limited data access, lack of organizational support, and weak inter-agency collaboration continue to hinder optimal outcomes. The study concludes that integrating forensic accounting into internal audit mechanisms and enhancing collaboration among stakeholders can significantly strengthen fraud prevention and detection systems in the banking industry.